Nucleotídeos purificados na dieta de fêmeas de tilápia do nilo em reprodução - Lima, Simone Antonello de (2018)
The objective of this study was to evaluate the growth and reproductive performance of Nile tilapia (Oreochromis niloticus) females fed with diets containing purified nucleotides, considering its effect on the immune system and oxidative stress. In this experiment, 420 females (286g ± 7.15) and 140 males (536g ± 13.4) of Nile tilapia of the GIFT line were used in the reproductive phase, housed separately in hapas installed in an excavated nursery. Breeders and matrices were fed diets containing 280g of digestible protein (PD) and 11.72 MJ of digestible energy (ED) per kg of feed and five levels of inclusion of purified nucleotides (0.0, 2.5, 5.0, 7.5 and 10g/kg of feed). Males and females were submitted to reproductive management in "hapas", remaining 12 days apart and 5 days in mating. At the end of the mating the eggs were collected and incubated. This procedure was repeated over five months. The animals fed rations containing 7.5 and 10g/kg of nucleotides presented higher weight gain, lower feed conversion (feed:body weight) and higher feed conversion in eggs (feed:no. eggs). These animals also presented (p<0.05) lower relative fecundity and lower percentage of spawning females. Plasma concentrations of alanine aminotransferase and alkaline phosphatase decreased (p<0.05), whereas hepatic and gonadal glycogen levels increased (p<0.05) in fish fed diets containing 5.0 and 7.5g/kg of nucleotides. Hemoglobin and plasma albumin concentrations increased (p<0.05) in a manner directly proportional to the inclusion of nucleotides. On the other hand, plasma triglyceride concentrations decreased (p<0.05) in animals fed 7.5g/kg. The catalase activity was lower (p<0.05) in the gonads of animals fed with 5.0g/kg of nucleotides, whereas lipid peroxidation was higher (p<0.05). Concentrations of superoxide dismutase also increased (p<0.05) in the liver of animals treated with 5.0, 7.5g/kg and 10g/kg of nucleotides. The higher level of inclusion of nucleotides promoted the increase (p<0.05) of glutathione transferase concentration in the liver and decreased (p<0.05) the concentration of nitrite/nitrate in the spleen. Finally, feeds did not influence the morphology of hepatic tissue and the height of intestinal villi, but animals fed 10g/kg of nucleotides had gonads with the highest (p<0.05) quantity of developing vitellogenic oocytes. The addition of nucleotides to the diet of Nile tilapia did not inhibit vitellogenesis. The low fecundities occurred due to the reduced mating period, since the ovaries presented large numbers of vitellogenic oocytes. Dietary supplementation of nucleotides promoted gains in growth, improvement in feed conversion and improvements in fish health. Even so, attention should be given to dietary supplementation at levels above 7.5g/kg, as they may cause liver and immune system disorders in the medium and long term.